MODEL PEMBELAJARAN STEAM DI RA MUSLIMAT 01 TUMPAKREJO KECAMATAN GEDANGAN KABUPATEN MALANG (Studi Kasus Konsep Pembelajaran Model STEAM Untuk Kelompok A) - Agustin, Yayuk; Sari, Ratih Permata (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2023)
STEAM is a learning approach that includes Science, Technology, Engineering, Art and Mathematics through the media around us (loose parts). The aim of the research is to describe the STEAM model effectively in children. This allows children to be more free to be creative in getting to know various STEAM concepts such as observing, researching, exploring and solving problems. The research method used is descriptive-qualitative context. The data that will be generated will be narrated in real terms. The results showed a positive impact on the use of loose part media and story books through the STEAM model. The findings of the results include learning activities to be more interesting, learning more interactive, more efficient use of time, quality of learning, and children are more able to be creative according to their interests and talents. The positive impact that is also felt by educators is providing teaching guidelines in achieving learning objectives, explaining teaching structures, clearly conceptualized media structures, systematic teaching frameworks. The research conclusions of the STEAM model can be applied in a fun way by exploring concepts that adjust the capacity of a child's learning space.